PREVENÇÃO DO CÂNCER DE MAMA E DE COLO UTERINO NUMA INDÚSTRIA CIMENTEIRA - de Oliveira Sousa, Jéssica Maria Custódio; Nazaré Oliveira, Eliany; Marques Rodrigues, Ilâna; dos Santos Lima, Danyela; da Conceição Alves, Cleidiane; Linhares Mendes, Iana (SANARE - Revista de Políticas Públicas, 2015)
-